2018
DOI: 10.1002/jmcd.12090
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Treating Race‐Based Trauma in Counseling

Abstract: This study investigated 106 counseling professionals' experiences with identifying and treating race-based trauma and the relationship between training and treatment. Competency was assessed with the Race-Based Trauma Survey for Counselors. Although most participants reported working with clients who had symptoms associated with race-based trauma, many had not received training in identifying and treating race-based trauma among individuals of color. This finding highlights the disparities between health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 86 publications
(180 reference statements)
2
45
0
Order By: Relevance
“…Counselors should be prepared to address racial discrimination in counseling, yet training to that end may be inconsistent. Indeed, Hemmings and Evans ( 2018 ) found that only 18.9% of the counselors in their sample received training related to addressing race-based trauma in clinical work. Along with utilizing culturally appropriate clinical interventions and techniques, counselors should be familiar with advocacy competencies (Toporek et al 2009 ) and guidelines (World Health Organization 2003 ) in order to effectively advocate with and on behalf of their clients of color.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counselors should be prepared to address racial discrimination in counseling, yet training to that end may be inconsistent. Indeed, Hemmings and Evans ( 2018 ) found that only 18.9% of the counselors in their sample received training related to addressing race-based trauma in clinical work. Along with utilizing culturally appropriate clinical interventions and techniques, counselors should be familiar with advocacy competencies (Toporek et al 2009 ) and guidelines (World Health Organization 2003 ) in order to effectively advocate with and on behalf of their clients of color.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given the prevalence of race-based traumatic stress, it is likely that counselors will hear client reports of this specific type of trauma from their clients. Indeed, in the study of 106 mental health and school counselors in the United States, Hemmings and Evans ( 2018 ) found that 70.8% of the sample reported working with clients with race-based trauma. Given the risk for secondary traumatic stress and burnout among counselors exposed to clients’ accounts of trauma, it is important to assess whether reports of race-based traumatic stress carry the same risk.…”
Section: Race-based Traumatic Stressmentioning
confidence: 99%
“…Given the high rates of discrimination experienced by African Americans, many may feel hopeless in finding a clinician who understands these issues or finding relief from the mental health sequalae of racism. Indeed, few clinicians are trained or equipped to treat racial trauma (Hemmings & Evans, 2018).…”
Section: Access and Barriers To Carementioning
confidence: 99%
“…First, ongoing assessment of perceived discrimination as a psychosocial stressor and dissemination of culturally-relevant mental health resources are important for clinical practice with Latinxs (cf. Hemmings and Evans, 2018). Drawing from race-based trauma approaches (Hemmings and Evans, 2018), targeting the role of perceived personal discrimination and developing coping strategies may effectively help to reduce depression symptoms (Carter, 2007) and the risk of poor physical HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Hemmings and Evans, 2018). Drawing from race-based trauma approaches (Hemmings and Evans, 2018), targeting the role of perceived personal discrimination and developing coping strategies may effectively help to reduce depression symptoms (Carter, 2007) and the risk of poor physical HRQoL. Fortunately, trauma-informed mental health interventions targeting depression symptoms at primary care clinics have been found feasible and acceptable among Latinxs (Kaltman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%